Inflammation, DNA Damage, Helicobacter pylori and Gastric Tumorigenesis - Kalisperati, Polyxeni; Spanou, Evangelia; Pateras, Ioannis S.; Korkolopoulou, Penelope; Varvarigou, Anastasia; Karavokyros, Ioannis; Gorgoulis, Vassilis G.; Vlachoyiannopoulos, Panayiotis G.; Sougioultzis, Stavros (Frontiers in Genetics, 2017)
Helicobacter pylori (H. pylori) is a Gram negative bacterium that colonizes the stomach of almost half human population. It has evolved to escape immune surveillance, establishes lifelong inflammation, predisposing to genomic instability and DNA damage, notably Double Strand Breaks (DSBs). The epithelial host cell responds by activation of DNA Damage Repair (DDR) machinery that seems to be compromised by the infection. It is therefore now accepted that genetic damage is a major mechanism operating in cases of H. pylori induced carcinogenesis. Here we review the data on the molecular pathways involved in DNA damage and DDR activation during H. pylori infection.